UI sketching reskill for UX researchers - Hussein, Idyawati; Mahmud, Murni; Hj. Ibrahim, Huda; Ghazali, Masitah; Ahmad, Azizah (Association for Computing Machinery, Inc, 2019)
In this paper, we highlighted the importance of User Experience (UX) sketching as one of the skillsets required for UX researchers in project development especially in low participatory design awareness countries like Malaysia. This is due to the results from UX research activities that are not perceived to be impactful by developers, designers and other stakeholders in digital transformation projects especially by the government that has been suffering from vendor-centric Request for Proposal (RFP) tender for the past 60 years. In consequences, time taken by developers to code from requirements captured by business analysts is longer than visual representation produced by UX or UI designers, which shortens the requirement gathering process. In conclusion, we found that UX sketching that produces visual representation of user needs to be effective especially in participatory design approach and to reduce user frustrations.